Antibacterial properties of contact defensive secretions in neotropical Crematogaster ants - Y Quinet; RHSF Vieira; MR Sousa; NS Evangelista-Barreto; FCT Carvalho; MIF Guedes; CR Alves; JC de Biseau; A Heredia (Journal of Venomous Animals and Toxins including Tropical Diseases, 2012)
Crematogaster ants use their contact venoms to compete with other ants. Although those venoms are used primarily as repellent and toxic secretions, they may have other functions. The present study aimed to test the antibacterial property of abdominal venom of three neotropical Crematogaster ant species (C. distans, C. pygmaea and C. rochai) against gram-negative (Escherichia coli and Pseudomonas aeruginosa) and gram-positive (Enterococcus faecalis and Staphylococcus aureus) bacteria. Sterile filter paper was soaked with C. distans, C. pygmaea or C. rochai crude venom and placed on an agar dish that was inoculated with bacterial suspensions. The agar dish was incubated overnight at 37ºC and examined for zones of growth inhibition. For each tested venom and bacterial strain, three venom concentrations were used, with six replicates for each concentration: 1, 2 and 4 DGE (Dufour's gland equivalent). The venom of C. pygmaea, but not those of C. rochai and C. distans, inhibited the growth of all tested gram-positive and gram-negative bacterial strains. This is the first evidence of antibacterial properties of contact venoms in Crematogaster ants and it supports the claim that ant venoms are multifunctional. It is hypothesized that only C. pygmaea venom showed antibacterial activities due to its nesting habits.